Right to food and sustainable livelihoods: use of pastoral cycle approach to respond to communities’ needs isiolo county, Kenya - Muthusi, Damaris; Arasa, Robert; Murag’e, Stephen (Machakos University, 2018)
The constitution of Kenya provides that each and every person has a right to adequate and quality food. Sustainable Development Goals (SDGs) 1, 2 and 6 focus on ending poverty and hunger, and availability of clean water to all people. However, all these provisions are articulated in the presence of a global environment under constant threat of degradation from extreme and uncontrolled human development. In this context, the study underscores what the Laudato Si document refers to: The earth must not live in poverty, and must therefore not be neglected, exploited and left ecologically unkempt. While Africa has experienced economic growth in the past two and half decades, the number of people still suffering from extreme hunger and poverty is unjustified; and such growth has not facilitated comprehensive cushion for marginalized groups of people. The Eastern region has failed to arrest the declining state of food security, and has even, under the now phased out Millennium Development Goals, not articulated comprehensive strategy to increase the resilience of their communities against hard core hunger. This is a contrast from the West and Southern regions where, the former successfully achieved MDG 1 while the latter seems headed there by 2020. In Kenya, millions of families still suffer food insecurity, and are thus not able to maximize their potential and contribute to their families and communities effectively. This study was carried out in Isiolo County, and aimed to a) build and strengthen the capacities of Isiolo county residents on resilience to food insecurity; b) facilitate the creation and firming of local advocacy actions on their right to food and c) promote alternative thinking like use of green technological to increase food production among target communities and protect environment from adverse global warming.The study employed mixed methods of research – qualitative and quantitative techniques. The key findings showed that drivers of change shaping global progress towards food security are multifaceted and communities are drivers to this transformational journey. This study recommends a bottom-up approach to understanding the communities’ illbeing and accompanying them to realize their potential to claim their rights; hence engage with the service providers to supply the required amenities for their community transformation and sustainable development.
Keywords: Food insecurity; Pastoral cycle approach; Sustainable livelihoods